PENYULUHAN TENTANG PPH 23 DAN PELAPORAN SPT TAHUNAN ORANG PRIBADI PADA PT CAHAYA RIZKI SAHABAT ANREG - Rifka, Fakhrur Rozi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Taxation is the people's contribution to the state treasury based on law (which can be enforced) without receiving direct reciprocal services (consideration) that can be specifically indicated, and is used to cover public expenditures. Through this community service activity, the goal is to provide an understanding of Income Tax Article 23 to support work implementation at PT Cahaya Rizki Sahabat Anreg (CHR Office) and to offer insights into the process of reporting Income Tax Article 21 for managing personal staff responsibilities as individual taxpayers. The method for this activity involves preparation stages, material explanation, and a question-and-answer session on Articles 23 and 21 of income tax. The results demonstrate an increase in employee awareness regarding timely tax reporting compliance. This service highlights the need for financial literacy and education to foster sustainable government tax economics in line with the principles of the Directorate General of Taxes.Keywords: Tax Counseling, Income Tax Article 23, Annual Tax Return Reporting, Online Taxation System